2022
DOI: 10.1101/2022.02.07.479433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong genotype by environment interactions in the rice Global MAGIC population across seedling stage drought

Abstract: Crop adaptation is required to sustainably increase the rate of yield gains to meet projected future needs under the challenging conditions of climate change and competition for resources. Future adaptation will likely need to harness both highly polygenic traits and genotype-by-environment interactions (GxE), the study of which is aided by complex recombinant populations. We used the diverse Oryza sativa Global Multiparent Advanced Generation InterCross (MAGIC) population to study the genetic architecture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…Other shallow root phenotypes in our studycrown root number and crown roots per tillerwere not consistently related to productivity under drought in this study. Moyers et al (2022) reported crown root number to be correlated with growth and productivity under vegetative stage drought stress in the rice Global MAGIC population under dry direct-seeded conditions. Ruangsiri et al (2021) found that crown root number was reduced in KDML 105 chromosome segment substitution lines when planted in clay soil, but an increase in crown root number was found in the same population when planted in sandy soil condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other shallow root phenotypes in our studycrown root number and crown roots per tillerwere not consistently related to productivity under drought in this study. Moyers et al (2022) reported crown root number to be correlated with growth and productivity under vegetative stage drought stress in the rice Global MAGIC population under dry direct-seeded conditions. Ruangsiri et al (2021) found that crown root number was reduced in KDML 105 chromosome segment substitution lines when planted in clay soil, but an increase in crown root number was found in the same population when planted in sandy soil condition.…”
Section: Discussionmentioning
confidence: 99%
“…Other shallow root phenotypes in our study – crown root number and crown roots per tiller – were not consistently related to productivity under drought in this study. Moyers et al. (2022) reported crown root number to be correlated with growth and productivity under vegetative stage drought stress in the rice Global MAGIC population under dry direct-seeded conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We used the genotyping data generated for the Global MAGIC lines (S6 generation) using genotyping × sequencing (GBS) (Elshire et al., 2011) as described in (Moyers et al., 2022; Zaw et al., 2019). Briefly, we built GBS libraries using the restriction enzyme ApeKI for each Global MAGIC line and six biological replicates of each parent.…”
Section: Methodsmentioning
confidence: 99%